1995
DOI: 10.1016/s0042-6822(95)90001-2
|View full text |Cite
|
Sign up to set email alerts
|

Picornavirus 2A Proteinase-Mediated Stimulation of Internal Initiation of Translation Is Dependent on Enzymatic Activity and the Cleavage Products of Cellular Proteins

Abstract: Poliovirus and human rhinovirus 2A proteinases are known to stimulate translation initiation on the cognate viral Internal Ribosome Entry Segments (IRESes). The molecular mechanism of this translational transactivation was investigated in vitro using dicistronic mRNAs containing picornaviral IRESes as the intercistronic spacer and purified human rhinovirus type 2 and coxsackievirus B4 2A proteinases. The stimulation achieved on the HRV2 IRES in the presence of the cognate 2A proteinase at 1 microgram/ml was tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 20 publications
3
52
1
Order By: Relevance
“…Previous ®ndings have indicated that eIF4G is susceptible to rapid cleavage and disappearance of the full length protein, not only in picornavirusinfected cells Devaney et al, 1988;Kirchweger et al, 1994;Ziegler et al, 1995a) but also in uninfected HeLa cells following antisense RNAmediated down-regulation of eIF4E (De Benedetti et al, 1991), in brain following ischaemia and reperfusion (DeGracia et al, 1996), in erythroleukaemia cells induced to di erentiate with haemin (Benton et al, 1996) and in yeast subjected to nutritional deprivation (Berset et al, 1998). Thus eIF4G seems particularly susceptible to degradation, probably by a number of di erent proteolytic pathways depending on the cell type and stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Previous ®ndings have indicated that eIF4G is susceptible to rapid cleavage and disappearance of the full length protein, not only in picornavirusinfected cells Devaney et al, 1988;Kirchweger et al, 1994;Ziegler et al, 1995a) but also in uninfected HeLa cells following antisense RNAmediated down-regulation of eIF4E (De Benedetti et al, 1991), in brain following ischaemia and reperfusion (DeGracia et al, 1996), in erythroleukaemia cells induced to di erentiate with haemin (Benton et al, 1996) and in yeast subjected to nutritional deprivation (Berset et al, 1998). Thus eIF4G seems particularly susceptible to degradation, probably by a number of di erent proteolytic pathways depending on the cell type and stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…We have expressed the 2A protease from poliovirus in HeLa cells to cleave eIF4G. Proteolysis of eIF4G by this protease inhibits capdependent translation whereas IRES-driven translation is maintained or stimulated (Ziegler et al 1995;Ohlmann et al 1997). Upon eIF4G cleavage by the virally encoded protease 2A (Fig.…”
Section: Gag Translation Is Driven By Three Ires Located Within the Cmentioning
confidence: 99%
“…Picornavirus RNAs are translated by a mechanism of internal ribosome entry dependent on an ;450 nt cisacting RNA element located within the 59-untranslated region (UTR), originally designated as the "internal ribosome entry site" (IRES)+ However, it is generally agreed that the actual ribosome entry site is not the total length of this large segment, but, if operationally defined as the most 59-proximal point at which initiation can occur, the entry or landing site is an AUG codon located 25 nt downstream of the start of a pyrimidine-rich tract at the 39 end of the IRES (for recent reviews, see Ehrenfeld & Semler, 1995;Hellen & Wimmer, 1995;Jackson & Kaminski, 1995)+ As has been described previously, the 59-proximal part of the oligopyrimidine tract is essential for IRES function in several different picornavirus species (Iizuka et al+, 1989;Jang & Wimmer, 1990;Kühn et al+, 1990;Meerovitch et al+, 1991;Nicholson et al+, 1991;Pestova et al+, 1991;Pilipenko et al+, 1992), but, on the other hand, the sequences between the oligopyrimidine tract and the AUG codon are not highly conserved between closely related species or even between different strains of the same species, although the length of this segment is conserved (Sangar et al+, 1987;Pritchard et al+, 1992)+ It has been suggested that this ;25-nt stretch serves as an unstructured spacer element (Kaminski et al+, 1994)+ On the basis of their IRES sequences, picornaviruses can be divided into three different groups: (1) hepatitis A virus, (2) the cardiovirus [e+g+, encephalomyocarditis virus (EMCV)] and aphthovirus family [e+g+, foot-and-mouth-disease virus (FMDV)], and (3) the enterovirus [e+g+, poliovirus (PV)] and rhinovirus family+ Several differences have been observed in the in vitro translation characteristics between IRESes from these different groups (Borman et al+, 1995)+ While IRESdriven translation of cardio-and aphthovirus RNAs is accurate and extremely efficient in the reticulocyte lysate, translation driven by the poliovirus or rhinovirus IRES is inaccurate and inefficient unless the system is supplemented with HeLa cell or Krebs II ascites cell extracts (Brown & Ehrenfeld, 1979;Dorner et al+, 1984;Svitkin et al+, 1988;Borman et al+, 1993Borman et al+, , 1995+ Another difference is that cleavage of eIF4G by picornavirus encoded proteases strongly stimulates translation driven by the polio-and the rhinovirus IRESes (Borman et al+, 1995;…”
Section: Introductionmentioning
confidence: 99%